Pengembangan Aplikasi Pengolahan Data Siswa Berbasis Android Menggunakan Metode Prototyping - Muhamad Alda (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2023)
Tritech Vocational School is one of the vocational high schools that, in the process of storing and processing student data, uses the Microsoft Excel application, so that the processing of student data is still considered less effective and efficient. This is due to the difficulty of distributing student data to those who need it; in addition, student data is only stored on a certain computer device, resulting in a lack of security, completeness, loss, or damage to data because it can be accessed by unauthorized parties and can also result in data loss if the computer device is damaged. The purpose of this research is to create an Android-based application that Tritech Vocational High School can use to process student data and make it easier to distribute student data. Prototyping is the systems development approach used in this study. includes stages of requirement communication, quick planning, quick design modeling, construction of a prototype and deployment, delivery, and feedback, while the system testing method uses the black box testing method. Android applications are built using the Kodular Framework and the Airtable database. Via an Android device and accessible online, the application developed helps Tritech Vocational Schools process student data, such as adding, changing, or deleting, and facilitate the distribution of student data. Processing student data using an Android-based application has higher security than using the Microsoft Excel application because it provides restrictions on access rights.